2010
DOI: 10.1002/hec.1541
|View full text |Cite
|
Sign up to set email alerts
|

The impact of income on the weight of elderly Americans

Abstract: SUMMARYThis paper estimates the impact of income on the body weight and clinical weight classification of elderly Americans using a natural experiment that led otherwise identical retirees to receive significantly different Social Security payments based on their year of birth. We estimate models of instrumental variables using data from the National Health Interview Surveys and find no significant effect of income on weight. The confidence intervals rule out even moderate effects of income on weight and on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(38 citation statements)
references
References 57 publications
4
34
0
Order By: Relevance
“…For example, Cawley et al (18) used a natural experiment to conclude that income had no effect on the weight of elderly Americans. For the general US population, Variyam and Blaylock (19) found that income was negatively associated with diet quality after controlling for other sociodemographic variables because of a link between income and preferences for convenience foods, dining out and more expensive, fat-rich foods.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Cawley et al (18) used a natural experiment to conclude that income had no effect on the weight of elderly Americans. For the general US population, Variyam and Blaylock (19) found that income was negatively associated with diet quality after controlling for other sociodemographic variables because of a link between income and preferences for convenience foods, dining out and more expensive, fat-rich foods.…”
Section: Discussionmentioning
confidence: 99%
“…We emphasize two strands. First, we find many studies looking at the effect of family (household) income on obesity or BMI (e.g., Cawley, Moran and Simon, 2008;Schmeiser, 2008;Garcia Villar and QuintanaDomeque, 2009). Second, there is also a well established literature interested in the effect of BMI or obesity on wages and earnings (e.g., Atella, Pace and Vuri, 2008;Cawley, 2004;Garcia and Quintana-Domeque, 2006;Han, Norton and Stearns, 2009).…”
Section: Introductionmentioning
confidence: 95%
“…These conflicting effects may explain why research so far has found little or no evidence that income affects BMI or the likelihood of becoming overweight or obese. 16,17 A direction for future research is to determine whether these negligible or zero effects on weight are the result of negligible changes in diet and physical activity, or whether there are substantial changes that happen to cancel each other out (for example, that calorie consumption and exercise both increase, with no net change in weight).…”
Section: Economic Factors and Childhood Obesitymentioning
confidence: 99%